Intestinal arteriovenous malformation managed with palliative ligation and division of the feeding artery: a case report - Sy, Edgar D.; Lu, Wei-Hsun; Liu, Yi-Sheng; Shan, Yan-Shen (Frontiers in Pediatrics, 2025)
Arteriovenous malformation (AVM) is a congenital vascular anomaly characterized by an abnormal connection between arteries and veins, bypassing the capillary system. AVM is commonly found in the central nervous system, as well as in the peripheral vascular system and the gastrointestinal tract. Symptomatic intestinal AVM (I-AVM) may present as gastrointestinal bleeding, ranging from occult bleeding to hematochezia. Diagnosis depends on the severity of symptoms, hemodynamic status, and location and size of the lesion and involves either endoscopy, arteriography, or contrast-enhanced computed tomography. Treatment varies based on the diagnostic modality used, such as endoscopic coagulation/clipping, trans-arterial embolization, or intestinal resection. Bleeding I-AVM located in the terminal ileum and presenting with a single prominent feeding artery can be managed with palliative ligation and division of the feeding artery rather than using bowel resection to preserve the ileocecal valve. Lifetime clinical follow-up is necessary due to the recurrence of bleeding secondary to vessel interconnection via the vasa recta and non-degeneration of the AVM nidus.